CHEMICAL DIFFUSIVITIES OF 18 TRACE ELEMENTS IN GRANITOID MELTS - Mungall J.E.; Dingwell D.B.; Chaussidon M. (My University, 1999)
We have measured effective binary chemical diffusion coefficients for Be, B, Mg, Ca, Ti, Ge, Sr, Y, Zr, Nb, Cs, Ba, Nd, Tb, Lu, Hf, Ta, and W at concentrations below 1000 ppm in synthetic granitoid melts by performing infinite couple diffusion anneals. By imposing systematic variations in the viscosity of a granitic melt through changes in temperature and composition, we have created an internally consistent set of diffusivities that can be used to assess quantitatively the relationship between melt viscosity, melt composition, and tracer diffusivities. One set of experiments were performed at 1 atm in an anhydrous haplogranitic melt near to the eutectic composition under air at temperatures of 1600, 1400, and 1137°C. A second set of experiments investigated the independent effects of the addition of approximately 3.7 wt.% H2O at 1600 and 1300C at 1.0 GPa pressure, and of 20 wt.% Na2O at 1 atm at 1200, 960, and 810°C. Within experimental error the measured diffusivities are Arrhenian, and show clear dependencies on ionic charge and radius, as well as on the viscosity of the melt.Monovalent, divalent, and trivalent cations show increasing activation energies with increasing field strength, whereas cations with higher charges have activation energies subequal to that of viscous flow. The Eyring equation is moderately successful in relating diffusivities of high field strength cations to melt viscosity, but underestimates the diffusivities of other cations by up to 4 orders of magnitude. The database of diffusivities reported in this contribution can serve to calibrate empirical models for the prediction of tracer diffusivities over a large range in melt composition, temperature, and viscosity.